Polyglutamine Expansion in Huntingtin and Mechanism of DNA Damage Repair Defects in Huntington’s Disease - Pradhan, Subrata; Gao, Rui; Bush, Keegan; Zhang, Nan; Wairkar, Yogesh P.; Sarkar, Partha S. (Frontiers in Cellular Neuroscience, 2022)
Emerging evidence suggests that DNA repair deficiency and genome instability may be the impending signs of many neurological diseases. Genome-wide association (GWAS) studies have established a strong correlation between genes that play a role in DNA damage repair and many neurodegenerative diseases, including Huntington’s disease (HD), and several other trinucleotides repeat expansion-related hereditary ataxias. Recently, many reports have documented a significant role played by the DNA repair processes in aging and in modifying many neurodegenerative diseases, early during their progression. Studies from our lab and others have now begun to understand the mechanisms that cause defective DNA repair in HD and surprisingly, many proteins that have a strong link to known neurodegenerative diseases seem to be important players in these cellular pathways. Mutations in Huntingtin (HTT) gene that lead to polyglutamine repeat expansion at the N-terminal of HTT protein has been shown to disrupt transcription-coupled DNA repair process, a specialized DNA repair process associated with transcription. Due to the recent progress made in understanding the mechanisms of DNA repair in relation to HD, in this review, we will mainly focus on the mechanisms by which the wildtype huntingtin (HTT) protein helps in DNA repair during transcription, and the how polyglutamine expansions in HTT impedes this process in HD. Further studies that identify new players in DNA repair will help in our understanding of this process in neurons. Furthermore, it should help us understand how various DNA repair mechanism(s) coordinate to maintain the normal physiology of neurons, and provide insights for the development of novel drugs at prodromal stages of these neurodegenerative diseases.